(untitled) (Research, Society and Development, 2022)
Tuberculosis (TB), one of the leading causes of death worldwide, is caused by bacteria of the Mycobacterium tuberculosis complex. TB transmission is commonly facilitated in the prison environment, due to poor ventilation and overcrowding, among other factors. Nova Alta Paulista is made up of 30 municipalities, nine of which have prison units (PU), therefore, knowing the epidemiology of TB in Nova Alta Paulista and its correlation with the presence of PU is important to contribute to the adoption of public measures of prevention health more effective. This is a descriptive research and time series between 2001 and 2020 to study the association between TB and PU cases. The number of TB cases per municipality was extracted from the informatics department of the Brazilian Unified Health System. TB is more prevalent in municipalities that have PU, and the coefficient for determining the mean number of TB cases in the nine municipalities with PU showed a value 62 times greater than the value for the coefficient for determining the mean number of TB cases in the nine municipalities with PU. 21 municipalities without PU, showing that in these municipalities the chance of acquiring and transmitting tuberculosis is greater. In addition, PU employees can be vehicles for acquiring and transmitting TB to the general population. These findings should contribute to the adoption of public health strategies for a better understanding of the dynamics of this disease and the adoption of more effective measures for TB control.